2014
DOI: 10.1097/mpg.0000000000000352
|View full text |Cite
|
Sign up to set email alerts
|

Topical Mitomycin‐C Application in Recurrent Esophageal Strictures After Surgical Repair of Esophageal Atresia

Abstract: There is no benefit in the resolution of the stricture when adding mitomycin-C treatment compared with repeated esophageal dilations alone in historical controls. Further randomized controlled studies and a short- and long-term evaluation of safety are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 19 publications
0
30
1
3
Order By: Relevance
“…On the contrary, a series of studies have shown the beneficial effects of mitomycin C on caustic esophageal strictures and anastomotic strictures after surgical repair of the esophageal atresia in children, in which a cotton pledget containing the drug is inserted into the esophagus or mitomycin C is injected via catheter balloon. However, most of these studies were small in sample size or lacked a control group …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, a series of studies have shown the beneficial effects of mitomycin C on caustic esophageal strictures and anastomotic strictures after surgical repair of the esophageal atresia in children, in which a cotton pledget containing the drug is inserted into the esophagus or mitomycin C is injected via catheter balloon. However, most of these studies were small in sample size or lacked a control group …”
Section: Discussionmentioning
confidence: 99%
“…Mitomycin C is a chemotherapeutic agent that reduces the formation of scar when applied to surgical lesions. It has been widely used in children experience postoperative esophageal strictures who have undergone surgical repairs for esophageal atresia or those who have caustic esophageal strictures . In recent studies, mitomycin C has also been used for the treatment of esophageal strictures after ESD in adults .…”
Section: Introductionmentioning
confidence: 99%
“…Local injection of steroids[81] [82] and topical application of Mitomycin-C into the stricture site[83] have showed encouraging results, but long-term studies are needed to prove their efficacy and safety. Esophageal stenting (plastic or metal stents) has been reported to be effective in preventing stricture recurrence,[84, 85] [86] but additional evidence is required to confirm these data.…”
Section: Anastomotic Stricturesmentioning
confidence: 99%
“…Furthermore, the median number of dilations, although not statistically significant, was smaller in the historical cohort than in the MMC group [3.7 (range 3–7) and 5.4 (range 3–11), respectively]. Author concluded that in EA children adjuvant MMC treatment does not confer a real benefit compared with repeated dilations alone (86). …”
Section: Treatmentmentioning
confidence: 99%